Implications of Genotype and Climate Variability on Phenolic Compounds of Grain: a Sorghum Case Study - Wu, Gangcheng (Curtin University, 2017)
Sorghum is a drought and heat tolerant grain crop, the consumption of which affects nutritional status and health due to its polyphenols. However, increasingly variable climate including rising temperatures, reduced water availability and changing UV radiation, may alter these polyphenols. This research discovered that both sorghum genotype and environmental variability influenced sorghum grain polyphenol profile and concentrations. The results are highly relevant to breeders and farmers for future production of sorghum with targeted polyphenolic levels.